Faktor-Faktor yang Mempengaruhi Rendahnya Tingkat Pendidikan Masyarakat Bajo - La Sudu; Maliudin Maliudin; La Ode Wahidin; Muhamad Al Kausar (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2024)
The problem in this study is what factors affect the education level of the Bajo community. This study aims to discover the factors that affect the low level of education of the Bajo community and how to solve them. The theory used in this study is socio-cultural theory, which uses a qualitative descriptive method. The position of social and cultural sciences will encourage and identify the mapping of educational problems in the Bajo community. The results of this study show that the factors that cause the low level of education in the Bajo community are the lack of educational equity and economic, family, and environmental factors. An effort to solve the low level of education of the Bajo community is that the government must increase the equitable distribution of education, build school buildings, and help the family economy with the help of scholarships for coastal children.